Felix si Otilia - Mihu, Iulian (Romania : Studioul Cinematograpfic Bucuresti, 1972)
Felix and Otilia are cousins. The two youngsters fall in love with each other. However, the social and financial position of Felix does not make him a good match for Otilia, who is courted by Pascalopol, a Romanian nouveau riche. At the same time, Otilia's family is desperately searching for the hidden fortune of Otilia's step-father, who is now confined to bed. The film is an adaptation of the novel "Otilia's Enigma" by George Calinescu, which describes the Romanian families confronting economic, social, and political challenges of the early 20th century.
Keywords: Fiction films